2017
DOI: 10.4172/neuropsychiatry.1000290
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin, Duloxetine, and Diazepam Selectively Modulate Acid-Induced Hyperalgesia and Anxio-Depressive Comorbidity in Rats

Abstract: Objective:Patients with chronic widespread pain (CWP) syndrome often have comorbid with depression/ anxiety symptoms and unsatisfied. Effects of pregabalin, duloxetine and diazepam in the well-established acid-induced CWP model remain unclear. This study aimed to assess these medicines on mechanical hyperalgesia and psychiatric comorbidity in this CWP model. Methods:The CWP model was elicited by repeated injections of acidic solution into unilateral gastrocnemius muscle of a rat. Each medicine was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Investigations of the acidic saline model's ability to induce negative emotionality associated with FMS-like pain yielded mixed results, with negative affect being inconsistent across various behavioral assays. Studies were identified with contrasting results within measures of EPM [93][94][95][96][97], OFT [65,93,97,98], sucrose measures [93,97], and FST [65,93,97,98]. Differences in avoidance behavior were not produced by the administration of acidic saline [65,99].…”
Section: Acidic Saline Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations of the acidic saline model's ability to induce negative emotionality associated with FMS-like pain yielded mixed results, with negative affect being inconsistent across various behavioral assays. Studies were identified with contrasting results within measures of EPM [93][94][95][96][97], OFT [65,93,97,98], sucrose measures [93,97], and FST [65,93,97,98]. Differences in avoidance behavior were not produced by the administration of acidic saline [65,99].…”
Section: Acidic Saline Evaluationmentioning
confidence: 99%
“…Differences in avoidance behavior were not produced by the administration of acidic saline [65,99]. Antidepressants: [97] Benzodiazepines: [97] Anticonvulsants: [65,93,94,97,99] Alternative Devices: [98] Organics: [93] Other: [93][94][95][96][97]99] Non-significant: [96] [99] -Organics: [94] Inconclusive:…”
Section: Acidic Saline Evaluationmentioning
confidence: 99%
See 1 more Smart Citation